IMAGERIES IN WILLIAM WORDSWORTH’S POEMS - Alam, Nur; Iskandar, Iskandar; Abdullah, Abdullah (Journal of English Literature and Linguistic Studies, 2023)
Poem is a medium of communication used by the poet to express their idea in a beautiful language. One of the elements of poem is imagery, functions of imagery are to create a vivid, realistic description of the scene, appealing to as many of the readers senses as possible, describes the appearance of characters and settings, the sounds, smells, taste and feeling of the poet. The objective of this research were to identify the types of imagery and describe the functions of imagery found in William Wordsworth’s poems The researcher used qualitative method with descriptive approach in this research. The results of this study show that there are 4 types of imagery found, they are, visual imagery, auditory imagery, olfactory imagery and organic imagery. Visual imagery in poetry functions to represent objects seen by the surrounding of the the poet related to nature such as flowers, stars, animals, and plants, auditory imagery in poetry has a function to represent sounds that also come from nature around the poet such as voice of animals, waves, wind and lightning. Meanwhile, the olfactory imagery in the poem functions to represent the scent of plants such as the smell of straw. Organic imagery functions to describe the poet feelings related to nature where the author feel happy when he sees beautiful views. Function of imagery that appears in the poem is to describe the object, poet feeling, as well as to represent the sound and smell that the poet experience from nature.